Diseño de una propuesta de comercio electrónico como estrategia de Marketing Mix en la Ferretería San Francisco Ltda. (2022)
The present study entitled "proposal of electronic commerce as a market strategy in La Ferretería San Francisco Ltda.", allowed identifying the needs of customers by having a web page that facilitates electronic commerce of the products offered by the Hardware store and proposes strategies to reduce the observed weaknesses. The type of research was descriptive, using a non-experimental and univariate descriptive method. The population was made up of 300 clients of the hardware store, but the sample was made up of 139. A questionnaire made up of (9) questions was designed without including the socioeconomic ones. The results obtained identified the need to market products through a virtual platform to buy and pay for the products offered by the hardware store as another alternative, different from the traditional one, which is why the hardware store must have a person who manages Virtually said platform, which must have a design, sufficient information on the products and means of payment